Nerve conduction patterns in Guillain-Barré syndrome associated with zika virus infection in Cucuta, Colombia (2018)
Background: Zika virus (ZIKV) infection has been associated with an increased incidence of Guillain-Barré syndrome (GBS) but the relative frequency of acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and axonal GBS subtypes is controversial. Methods: Twenty-three GBS patients diagnosed according to Brighton criteria during the ZIKV outbreak in Cúcuta, Colombia, were evaluated clinically and electrophysiologically. Electrodiagnosis of GBS subtypes was made according to a recently described criteria set that proved to have a high diagnostic accuracy on the basis of a single test. The electrophysiological features of 34 Italian AIDP patients were used as control. Results: All patients had symptoms compatible with ZIKV infection before the onset of the GBS and the diagnosis of ZIKV infection was confirmed in 69.5 % of patients. Median time from onset of ZIKV infection symptoms to onset of GBS was 6 days (interquartile range, 6-14 days). Cranial nerve palsy was present in 82.6% of patients, facial palsy in 65.2%, autonomic dysfunction in 69.5%, and 43.4% of patients required mechanical ventilation. AIDP was diagnosed in 73.9% of patients. About 50% of nerves of the AIDP patients showed a prevalent demyelinating distal involvement but this pattern was not different from Italian AIDP patients without ZIKV infection. Conclusions: GBS associated with ZIKV infection is clinically characterized by a high frequency of cranial nerve involvement, autonomic dysfunction and necessity of mechanical ventilation indicating an aggressive and severe course. AIDP is the most frequent electrophysiological subtype. Demyelination is prevalently distal but this pattern is not specific of ZIKV infection.